PENGARUH PENGALAMAN DAN PENGETAHUAN AUDIT TERHADAP PENDETEKSIAN TEMUAN KERUGIAN DAERAH (STUDI PADA AUDITOR INSPEKTORAT ACEH) - Masrizal Masrizal (Program Magister Akuntansi Unsyiah, 2010)
This research aim to examine the influece of audit experience and audit knowledge to local losses findings detection simultaneously and partially.The populasi of research are all 48 auditors of Inspektorat Aceh as population who participate in regular inspection taken bya sensus. The data taken from questionaires distributed to responden. Variables in this research are the independent variable experience (X1) and audit knowledge (X2), while the bound variable (dependent) is the local losses findings detection (Y). Data were analized using multiple linear regression analisys (multiple regretion).The results showed that audit experience and audit knowledge are simultaneously and partially have significant impact on local losses findings detection.Value of the coeficient of determination indicates that together the audit experience and knowledge contribute to the local losses findings detection of 46,7 %, while the remaining 53,4 % are influenced by othe outside factor model.The audit experience and audit knouledge of Inspectorate Aceh auditors have important role to help auditor during their duty in detecting local losses findings. Keyword: audit experience, audit knowledge, and local losses findings detection